2015
DOI: 10.1007/s12306-015-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Chondropenia: current concept review

Abstract: The term "chondropenia" indicates the early stage of degenerative cartilage disease, and it has been identified by carefully monitoring early-stage osteoarthritis (OA). Not only is it the loss of articular cartilage volume, but it is also a rearrangement of biomechanical, ultrastructural, biochemical and molecular properties typical of healthy cartilage tissue. Diagnosing OA at an early stage or an advanced stage is valuable in terms of clinical and therapeutic outcome. In fact degenerative phenomena are suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 143 publications
0
14
0
Order By: Relevance
“…During OA development, progressive cartilage degeneration is observed. Histochemistry analyses have demonstrated the formation of chondrocytes clusters, the presence of irregular surfaces (fibrillations), cartilage volume loss, and matrix calcification in OA cartilage compared to normal cartilage [18]. These changes in cartilage structure are linked to the alteration of molecular components of ECM.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…During OA development, progressive cartilage degeneration is observed. Histochemistry analyses have demonstrated the formation of chondrocytes clusters, the presence of irregular surfaces (fibrillations), cartilage volume loss, and matrix calcification in OA cartilage compared to normal cartilage [18]. These changes in cartilage structure are linked to the alteration of molecular components of ECM.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Typically, the decrease in proteoglycan becomes prominent with disease progression and can be evidenced by reduced Safranin-O staining [19]. Distribution of the collagen II network is modified, being uniformly distributed throughout the normal cartilage layers, but at a decreased level in OA-degenerated areas and at an increased level in chondrocytes clusters [18]. Breakdown of these components are handled by a set of aggrecanases (e.g., a disintegrin and metalloproteinase with thrombospondin motifs ADAMTS-4 and -5) and collagenases (e.g., matrix metalloproteases, MMP-1, -3, -8, and -13), which are upregulated, even in early stages of OA-associated cartilage degradation.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Furthermore, changes in the number of viable articular chondrocytes in experimentally induced arthritis [99], human RA [100], and OA are almost certainly associated with the autophagicmediated cell death of chondrocytes [101][102][103][104][105], which occurs in concert with the activation of the extrinsic apoptosis pathway, the latter mediated by Tumor necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL), Death Receptor-5 (DR5) and caspase-3 [106,107]. In that regard, it was noteworthy that Huang et al [108] reported that exogenous leptin promoted chondrocyte apoptosis while inhibiting chondrocyte autophagy via the up-regulation of lysyl oxidase-like 3 (LOXL3).…”
Section: The Relationship Between Apoptosis and Autophagymentioning
confidence: 99%
“…Although various factors cause OA, aging is the most common factor associated with the development of OA; other factors, such as mechanical stress and hereditary and environmental factors, also lead to the development of OA ( 1 , 2 ). OA is primarily characterized by joint swelling due to a progressive breakdown and loss of articular cartilage, involving increased synovial inflammation, subchondral bone sclerosis and osteophyte formation, which leads to chronic pain and functional limitations in the joint ( 3 , 4 ). Furthermore, the dysregulation of glucose and energy metabolism also aggravate the symptoms in patients with OA ( 5 ).…”
Section: Introductionmentioning
confidence: 99%